Acute and Chronic Toxic Effects of Chloramphenicol on Scenedesmus Obliquus and Chlorella Pyrenoidosa. (1st August 2013) - Zhang, Wei; Sun, Wenfang; An, Shuai; Xiong, Bang; Lin, Kuangfei; Cui, Xinhong; Guo, Meijin
ABSTRACT: : The acute and chronic toxicological effects of Chloramphenicol (CAP) on Scenedesmus obliquus and Chlorella pyrenoidosa are not well understood. The indoor experiments were carried to observe and analyze the CAP induced changes. Results of the observations have showed that CAP exposure could significantly inhibit the growth of Scenedesmus obliquus in almost all the treated groups, while Chlorella pyrenoidosa exhibited less sensitivity. Chlorophyll‐a syntheses of Scenedesmus obliquus were all inhibited by CAP exposure, while Chlorella pyrenoidosa displayed obvious stimulation effect. Catalase (CAT) and Superoxide dismutase (SOD) activities of both algae were promoted in all the treatments. The experimental results indicated that the growth and Chlorophyll‐a syntheses of Scenedesmus obliquus were more sensitive in response to CAP exposure than that of Chlorella pyrenoidosa . While for CAT and SOD activities, Chlorella pyrenoidosa showed more susceptible. This research provides a basic understanding of CAP toxicity to aquatic organisms.